What is next in sepsis: current trials in sepsis. Issue 8 (August 2012) - Artigas, Antonio; Niederman, Michael S; Torres, Antoni; Carlet, Jean
17th International Symposium on Infections in the Critically Ill Patient Barcelona, Spain, 3–4 February 2012 International experts reviewed and updated the most recent and relevant scientific advances on severe sepsis during the 17th International Symposium on Infections in the Critically Ill Patients in Barcelona (Spain) in February 2012. All new pharmacological therapeutic strategies have failed to demonstrate a survival benefit. Despite the large variability among countries and hospitals, the improvement of standard care according to the Surviving Sepsis campaign recommendations reduced the 28-day mortality to 24%. These results may have implications for future clinical trials in which much larger samples sizes of patients at high risk of death will be necessary. The identification of novel proinflammatory endogeneous signals and pathways may lead to the discovery of new drugs to reduce inflammatory reactions and end-organ dysfunction in critically ill patients with sepsis. Extracorporeal blood purification stem or progenitor cells have received increasing interest for the treatment of inflammation and organ injury. A better understanding of how these therapies work is essential and its benefit should be confirmed in future prospective randomized studies.